Evidence-Based Recommendations for the Management of Knee Osteoarthritis: A Consensus Report of the Turkish League Against Rheumatism - Rezzan GÜNAYDIN,; Zeliha ÜNLÜ19,; Hatice UĞURLU,; Ömer Faruk ŞENDUR,; Serap SÜTBEYAZ,; Birkan SONEL TUR,; Dilşad SİNDEL,; Merih SARIDOĞAN,; Neşe ÖLMEZ,; Yeşim KURTAİŞ,; Taciser KAYA,; Sami HİZMETLİ,; et al. (Archives of Rheumatology, 2012)
Objectives: Knee osteoarthritis (OA) is a common disease which causes pain, disability and great socioeconomic burden as a result. Turkish League Against Rheumatism (TLAR) initiated a project to prepare national, “evidence-based recommendations for the management of knee osteoarthritis” supported by expertopinion in order to assist the physicians who are interested in knee OA in their daily clinical practice. Materials and methods: The expert committee was composed of 25 academicians, 23 of whom were physical medicine and rehabilitation (PM&R) specialists (three also had rheumatology subspeciality) and two were orthopedic surgeons. At the first meeting, the previous guidelines were discussed, and 2008 Osteoarthritis Research Society International (OARSI) recommendations were decided to be taken as the fundamental template for national recommendations. Databases of the Pubmed, Embase, Cochrane, and Turkish Medical Index were used to search the literature, and this was carried out for the period between 2009-2010 for international publications since studies up to 2009 were present in the 2010 OARSI update. No limit was applied for searching of national publications. The selected relevant publications were graded according to evidence level and quality, and were sent to the members who were then asked to suggest propositions according to their experiences, knowledge, and review of the literature. After amalgamation and editing of new proposals, Delphi rounds were started. After five Delphi rounds, the propositions on which the members were in consensus, were discussed with regard to evidence and the “strength of recommendation” was determined by measuring on visual analog scale (VAS) for each proposal at the final meeting. Results: Nineteen propositions (one for general principles, nine for nonpharmacologic treatments, seven for pharmacologic treatments, and two for surgical treatments) were accepted as the “TLAR Evidence-Based Recommendations for the Management of Knee OA” in consensus as a result of Delphi rounds. Conclusion: Evidence-based recommendations for the management of knee OA were developed by TLAR for the first time in our country. The recommendations should be updated regularly according to new evidence and insights. It is expected that physicians who are interested in knee OA will benefit greatly from this report in their daily clinical practice.